Self-loading microfluidic platform with ultra-thin nanoporous membrane for organ-on-chip by wafer-level processing - Tang, Bo; Bendas, Sebastian; Krajka, Victor; May, Tobias; Moritz, Anke; Constantinou, Iordania; Reichl, Stephan; Dietzel, Andreas (Frontiers in Sensors, 2022)
Embedded porous membranes are key element of various organ-on-chip systems.The widely used commercial polymer membranes impose limits with regard to chip integration and thinness.We report a microfluidic chip platform with the key element of a monolithically integrated, ultra-thin (700nm) nanoporous membrane made of ultra-low-stress (<35MPa) SixNy for culturing and testing reconstructed tissue.The membrane is designed to support various in vitro tissues including co-cultures and to allow passage of molecules but not of cells. A digital laser write method was used to produce nanopores with deterministic but highly flexible positioning within the membrane.A thin layer of photoresist was exposed by accumulation of femtosecond pulses for local two-photon polymerization, which allowed nanopores as small as 350nm in diameter to be generated through the membranes in a subsequent plasma etch process.The fabricated membranes were used to separate a microfluidic chip into two compartments, which are connected to the outside by microchannel structures.With unique side inlets for fluids, all 15 cells are exposed to identical flow velocities and shear stresses.With the hydrophilic nature of chip materials the self-loading seeding is controlled bottom-up by capillary forces,which makes the seeding procedure homogeneous and less dependent on the operator.The chip is designed to allow fabrication by wafer-level MEMS manufacturing technologies without critical assembly steps,thereby promoting reproducibility and scale-up of fabrication. In order to establish a fully functional test system to be used in a lab incubator, a holder for the bare chip was designed and 3D-printed with additional elements for gravity driven pumping. In order to mimic physiological conditions,the holder was designed to provide not only media delivery but also appropriate shear stress to the tissue.To prove usability, murine microvascular endothelial cells (muMEC) were seeded on the membrane within the chip.Cell compatibility was confirmed after three days of dynamic cultivation using fluorescence live/dead assays. Cultivation proved to be reproducible and led to confluent layers with cells preferentially grown on nanoporous areas.The system can in future be cost effectively manufactured in larger quantities in MEMS foundries and can be used for a wide variety of in vitro tissues and test scenarios including pumpless operation within cell incubator cabinets.